Ilustratorki. Analiza wybranych przykładów ilustracji artystycznie wartościowej we współczesnej polskiej książce dziecięcej - Steliga, Anna (Warstwy, 2019)
The issue of illustrations in children’s books often comes up in all sorts of publications, at conferences and exhibitions. Therefore it is worth raising the topic of artistically valuable Polish illustrations, which are accessible to the child and have a positive effect on its development. Illustrations shape the aesthetic taste of the child. A properly made picture book makes an integral whole, where the text is inseparable from the image, creating unity. This gives the child an opportunity to have a fuller sense and deeper understanding of what the book is about. The article presents the works of such illustrators as: Ewa Kozyra-Pawlak, Anna Niemierko, Grażka Lange, Elżbieta Wasiuczyńska, Małgorzata Bieńkowska and Marta Ignerska, demonstrating the important role of illustrations in contemporary Polish children’s books.